If it's not what You are looking for type in the equation solver your own equation and let us solve it.
32+(18-6)/2=0
We simplify the equation to the form, which is simple to understand
32+(18-6)/2=0
Simplifying terms in parentheses
32+(+12)/2=0
Reorder the terms in parentheses
32+(+6)=0
Remove unnecessary parentheses
+32+6=0
We move all terms containing to the left and all other terms to the right.
0=0-32-6
We simplify left and right side of the equation.
0=-38
0=-38
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 1/-7/8=4/9 | | 60+(25-10)/5= | | 3x-6(19)=48 | | 4x+1-x=-23 | | -(6x-5)-(2x-5)+9=-8(x-1)-(4x+8)+3 | | 56+(40-12)/4= | | 9x-23=x+1 | | xsquared+9x+16=8 | | 3+2x=3(2+x) | | 7*(18+4)-13= | | 9+5x-3x=27 | | 4n+n+4=16-(n) | | 3x+4=-32 | | -6x-30= | | -6x+10=-56 | | 12x^2y^2+29x^2y= | | 4n+n+4=16-n | | 2(6y+3z-1)=12y+3z-1 | | 3x+70-7x= | | x-(8)=-2 | | 4x-8x=-24 | | 4x/7-4=12 | | 8n-4=12 | | x-(9)=-7 | | 12c-6=10c+4 | | 3a+11=4a+8 | | 4/5x+3=5x | | 4g-9=(-3g)+12 | | 2/3(3x+12)=32 | | 3(x+5)+4=3x+4 | | .2x^2+16x=0 | | 42=-6(-2x-3) |